A novel Ag(i)-calix[4]arene coordination polymer for the sensitive detection and efficient photodegradation of nitrobenzene in aqueous solution. Issue 1 (1st December 2016) - Liu, Lei-Lei; Chen, Jing; Yu, Cai-Xia; Lv, Wen-Xing; Yu, Hui-Ying; Cui, Xiao-Qing; Liu, Lin
Abstract : A bi-functional coordination polymer for the detection and photodegradation of NB was designed and synthesized from AgNO3 and tetra-pyridyl calix[4]arene. Abstract : Nitrobenzene (NB) is a widespread and highly toxic organic pollutant in water, and consequently its detection and removal have attracted considerable attention. In the present study, we designed and synthesized a novel coordination polymer, [AgL0.5 (NO3 )] n (1 ), L = 25, 26, 27, 28-tetra[(3-pyridylmethyl)oxy]calix[4]arene, from AgNO3 and a tetra-pyridyl-functionalized calix[4]arene ligand, which possessed a 2D network based on [Ag4 L(NO3 )4 ] units. The1 -modified glassy carbon electrode (1 /GCE) exhibited good electrocatalytic activity toward the reduction of NB, offering the selective detection of NB in a wide linear range (1–2450 μM) and a low detection limit (0.62 μM). Furthermore, it displayed excellent photocatalytic activity for the degradation of NB in aqueous solution under UV light. The kinetics of the catalytic degradation reaction and the stability of the catalyst were also studied. These results indicated that compound1 is a favorable material for the effective determination and degradation of NB, which makes it a promising candidate in both monitoring water quality and treating wastewater.